The Influence of Health Professional Ethics on Controversial Medical Decisions - Bubun Bunyamin; Hj.Yeti Kurniati; Hj.Hernawati Ras (Formosa Journal of Social Sciences (FJSS), 2023)
This study investigates the implications of differences in ethical values between healthcare practitioners, patients, and families related to the use of advanced medical technology in medical decision making. In the context of complex medical decisions, this research reviews how moral, social, and medical factors influence the decision-making process, especially in situations of terminating care for patients in terminal condition. Through a multidisciplinary approach, this study investigates how healthcare practitioners navigate ethical dilemmas, consider patient perspectives, and integrate ethical values in clinical practice. The results of this study provide deep insight into the complex dynamics of medical decision making and encourage the adoption of a holistic approach in responding to differences in ethical values